Developing Tejas Spa to Enhance Service Quality and Maximize Hotel Revenue at Adiwana Suweta Ubud - I Gede Eka Rosdiana Putra; Ni Gst Nym Suci Murni; I Ketut Suja (Journal of Social Research, 2026)
This study aims to analyze the development and operational performance of Tejas Spa Suweta as a strategic wellness facility within Adiwana Suweta, with a focus on enhancing service quality and maximizing revenue generation, as well as to propose an applicable project outcome model for spa operations in similar hospitality settings. The project implementation is guided by the POAC (Planning, Organizing, Actuating, and Controlling) management framework, supported by the SERVQUAL model to assess service quality, the Marketing Mix 4P for strategic positioning, and the Triple Bottom Line concept to ensure sustainability. From a financial perspective, the spa demonstrates strong revenue performance, generating approximately IDR 1.46 billion within six months, with an outlet income margin of approximately 71.65%. These results confirm that high service quality and operational integration contribute significantly to revenue generation.This study proposes a Project Outcome Model consisting of three interconnected layers: input (service quality), operational integration system (interdepartmental coordination), and output (service excellence and revenue generation). The model highlights the reciprocal relationship between service excellence and financial performance, forming a continuous improvement cycle. This research contributes to the hospitality and wellness industry by providing practical insights and an applicable model for spa development, demonstrating how the integration of service quality, operational systems, and strategic management can enhance both guest satisfaction and financial performance.